Mindfulness, Regulasi Diri, dan Kesejahteraan Akademik: Tinjauan Sistematis pada Pelajar dan Mahasiswa - Gustriya Wijayanto (STAB Kertarajasa, 2026)
This study aims to systematically examine the role of mindfulness in supporting students’ self-development through a Systematic Literature Review (SLR). The review synthesizes research articles on the implementation of mindfulness in educational contexts, ranging from elementary to higher education. The findings indicate that mindfulness contributes substantially to reducing academic anxiety and stress, while enhancing learning concentration, cognitive performance, learning motivation, and academic engagement. In addition, mindfulness plays a key role in strengthening self-regulation, emotional regulation, resilience, and students’ psychological well-being. The synthesis further reveals that integrating mindfulness into learning processes and character education positively supports the development of ethical values, empathy, discipline, and responsibility. These findings position mindfulness as a relevant psychological and pedagogical approach for promoting holistic learning and academic mental well-being. This study provides a thematic synthesis that may serve as a reference for educational practice and future research, and recommends the contextual integration of mindfulness in education with careful consideration of cultural aspects and the sustainability of its implementation.